‘Many dark ribbons’ ou le format mis en fiction : The Golden Apples de Eudora Welty - Jean-Marc Victor (Interfaces)
In reaction to the novel’s editorial tyranny in American fiction, a number of writers in the first half of the 20th century shifting away from conventional narrative forms explored the possibilities of the short story cycle : within this peculiar narrative format, each story can be read independently but its meaning is modified and/or expanded through its relations to the other texts composing the volume. Reading becomes discontinuous and fragmentary. Various types of echoes invite the reader to reconstruct some degree of unity as such unity is not provided from the start, which requires a much higher level of reader participation than in the case of a novel. This article proposes to analyze the complex ways in which Eudora Welty plays with such a format in her own 1949 short story cycle The Golden Apples. How does this unstable cyclical format interact with the book’s thematics, oscillating between interrelatedness and separateness and, as a result, how does it challenge the reader’s own reception of this narrative construct that turns its back on novelistic norms?